Recent and Upcoming Therapies for Management of Type 2 Diabetes: A Review - Rutul Gokalani; Mahira Saiyed; Amit Dey; Firdous Sheikh (Preventive Medicine: Research & Reviews)
The article encompasses the present and future pharmacotherapies involved in managing type 2 diabetes (T2D). It is divided into three sections: recent treatment modalities of the last decade, upcoming approved drugs to be available in India, and near future drugs under clinical trials. It highlights the oral hyperglycaemic agents and insulin options available in India, their potential effects on diabetes outcomes and the clinical trials. India is a fast and dynamic adopter of novel treatments and newer technologies with off-patent and in-patent modalities. Medicinal novelties surround T2D, but technological advancements have touched newer heights with surreal support of artificial intelligence-based innovations, especially in type 1 diabetes management.